EFFECT OF DIGITAL DISTRIBUTION CHANNELS ON PERFORMANCE OF INSURANCE SECTOR - Kajwang, Ben (Journal of Marketing Studies, 2022)
Purpose: The insurance business is critical to the growth of any nation's economy. All insurance companies rely heavily on distribution to be a part in their overall performance. As technology has advanced, insurers have begun looking into new avenues of distribution in the internet sphere. The study's goal is to assess the effect of digital distribution channels on performance of insurance sector. Methodology: A desktop literature review was used for this purpose. Relevant seminal references and journal articles for the study were identified using Google Scholar. The inclusion criteria entailed papers that were not over 10 years old. Findings: All insurance companies rely heavily on distribution to be a part in their overall performance. It is now feasible for consumers to acquire an insurance policy directly online, without the need for a middleman or physical distributor, thanks to a growing number of agency businesses and direct insurance writers. The insurance sector has benefited from the following new technological developments in recent years. Technology is increasingly significantly reliant on the digital channel of distribution for the purchase of insurance and policy management. Unique contribution to theory, practice and policy: Both public and private life insurance businesses must boost Internet marketing and on-site marketing as sales platforms. Life insurance businesses in both the public and private sectors should offer tax-saving programs tailored to the needs of their consumers. Digital distribution channels should be taken into account by policymakers in their strategy formulations because of technical advancements and the predicted shift away from physical branch networks to technologically enabled insurance services.